A winter storm in Alderney Race: Impacts of 3D wave–current interactions on the hydrodynamic and tidal stream energy. (March 2022) - Bennis, A.-C.; Furgerot, L.; Bailly Du Bois, P.; Poizot, E.; Méar, Y.; Dumas, F.
Abstract: Due to the climate change, it is necessary to modify the energy modes of production. The mix energetic, based on renewable energies as tidal currents, is one of the solutions to decrease the energy production carbon footprint. This article focuses on hydrodynamic interactions in Alderney Race (France), which is the most energetic tidal site in Western Europe with a maximum potential of 5 . 1 GW according to Coles et al. (2017). The impact of a winter storm occurring during spring tide is assessed thanks to numerical modeling with a 3D fully-coupled wave–current model and in-situ data. This study starts to analyze the impacts of the storm on the wave field and the current effects on waves. Then, the modifications of the current and tidal stream energy caused by waves are discussed. After a successful validation step with excellent PBIAS and R 2 scores, the main finding are: (i) although the current intensity is strong (around 3– 4 m s − 1 ), the wave action significantly changes the vertical profile of the current, with a reduction of the PBIAS by a factor of 1.78 between simulations with and without wave effects, (ii) ocean waves affect the tidal asymmetry, with a flood current whose intensity is 13% higher than for the ebb current, inducing a decrease of 30% in the tidal stream energy, (iii) the flow is very sensitive to the angle between the directions of propagation of waves and current, with an acceleration or a reduction of the velocity, as observed in the presence of a 3D turbulent structure, (iv) current effects on waves cause a wavenumber shift, changes in significant wave height (modulated by tide), wave direction due to refraction and an increase of the energy transfer from waves to ocean ascribed to the wave breaking. By a feedback mechanism, the modifications of the wave field by current and water level significantly alter the flow with a decrease of its velocity when waves propagate against current. This study shows that the 3D wave–current interactions need to be considered during a storm even during a spring tide event where currents are the strongest. Highlights: Impacts of the Eleanor's storm on the hydrodynamic and tidal stream energy in Alderney Race were assessed. During the Eleanor's storm, ocean wave effects resulted in a reduction in tidal stream energy of up to 30%. Ocean wave effects increased tidal asymmetry estimated at 3% under calm conditions to 13% under current storm conditions. Even during spring tide in Alderney Race, ocean wave effects during storm conditions must be considered.